2002
DOI: 10.1093/bja/88.5.724
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy, lingular tonsillectomy and sleep-related breathing disorders

Abstract: Laser resection of lingual tonsils and formal closure of a tracheostomy improved the airway in a 14-yr-old patient with Down's syndrome. Non-invasive airway support to treat obstructive sleep apnoea was postponed with this treatment. During the anaesthetic a laryngeal mask airway was used to support the airway after lingual tonsillectomy, to assess the suitability of defunctioning the tracheostomy. Laryngeal mask airways assist management of lingual tonsils. Lingual tonsillar hypertrophy can lead to obstructiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Neuromuscular blocking agents were avoided during induction of general anesthesia to preserve the skeletal muscle support of the upper airway, as it has been reported that the loss of upper airway skeletal muscle support in some cases of LTH may be fatal. In these situations, the lingual tonsils may act as a ball-valve effect obstructing the glottic opening and interfere with oxygenation [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuromuscular blocking agents were avoided during induction of general anesthesia to preserve the skeletal muscle support of the upper airway, as it has been reported that the loss of upper airway skeletal muscle support in some cases of LTH may be fatal. In these situations, the lingual tonsils may act as a ball-valve effect obstructing the glottic opening and interfere with oxygenation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques for lingual tonsillectomy have been performed, sharp dissection was used by Dundar et al [7], while Conacher et al [17] used laser; they reported that hemorrhage and post-operative edema were less frequent. Recently, Lin and Koltai [26] used endoscopic-assisted coblation lingual tonsillectomy for treatment of cases with LTH; although the method was effective in relieving symptoms with no reported post-operative edema, 2 out of 26 cases developed adhesions between tongue base and epiglottis, however this complication did not affect feeding or breathing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conacher also describes a patient with Down's syndrome who presented with progressive obstructive sleep apnea caused by hypertrophied lingual tonsils. 30 The patient presented no further symptoms of obstruction three months later. Nakazawa also submits a patient with Down's syndrome and obstructive sleep apnea due to LTH.…”
mentioning
confidence: 84%
“…Comparison of pre-operative and post-operative PSG demonstrated statistically significant reductions in the respiratory distress index (12). Complications related to lingual tonsillectomy include edema (67) and adhesions between the epiglottis and tongue base (68). …”
Section: Surgical Techniquesmentioning
confidence: 99%